2013
DOI: 10.1186/1617-9625-11-9
|View full text |Cite
|
Sign up to set email alerts
|

Future physicians and tobacco: an online survey of the habits, beliefs and knowledge base of medical students at a Canadian University

Abstract: BackgroundLittle is known about the knowledge and attitudes towards tobacco use among medical students in Canada. Our objectives were to estimate the prevalence of tobacco use among medical students, assess their perceived level of education about tobacco addiction management and their preparedness to address tobacco use with their future patients.MethodsA cross-sectional online survey was administered to University of Alberta undergraduate medical school trainees. The 32-question survey addressed student demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
1
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 25 publications
2
32
1
8
Order By: Relevance
“…Recent evidence supports this estimation, data from the Canadian youth smoking survey showed that in 2012-2013, about 24 % of students in grades 6-12 ever tried a cigarette and 4 % were current cigarette smokers, those numbers for WP were 9 and 3 % for ever tried and current use, respectively [17]. However, emerging evidence in some subpopulations, including medical students and athletes showed that the prevalence of WP smoking has surpassed cigarettes smoking [26,32]. Nonetheless what is worrisome in the case of WP is the trend.…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Recent evidence supports this estimation, data from the Canadian youth smoking survey showed that in 2012-2013, about 24 % of students in grades 6-12 ever tried a cigarette and 4 % were current cigarette smokers, those numbers for WP were 9 and 3 % for ever tried and current use, respectively [17]. However, emerging evidence in some subpopulations, including medical students and athletes showed that the prevalence of WP smoking has surpassed cigarettes smoking [26,32]. Nonetheless what is worrisome in the case of WP is the trend.…”
Section: Discussionmentioning
confidence: 77%
“…WP use poses many challenges for the tobacco control community, including the potential that it may become a gateway to other forms of tobacco/drug use and a cause of relapse for cigarette smokers who had previously quit [3,10,20]. In some sub-populations in Canada and the US, WP use surpasses cigarettes use [9,32]. Few measures are in place to deal with WP smoking.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Moreover, smoking can present significant risk factors for dental caries (24). The overall prevalence of smoking rate among medical students in other countries was lower and ranged from 3.3% in Canada to 19.3% in Turkey (25,26). The implementation of a tobacco curriculum and smok- ing cessation counselling for medical students would probably reduce the number of smokers and would be effective in preventing smoking initiation.…”
Section: Discussionmentioning
confidence: 99%
“…5,[11][12][13] A recent survey of German medical schools revealed that lectures are the predominant teaching method 14 when a more practical approach to teaching seems more appropriate for students to learn how to deliver VBA. 15 The fact that knowledge and skills related to counseling and pharmacotherapy are addressed in summative assessments in only half of all medical schools is of some concern as it has been shown that teaching itself is much less effective than reinforcing student learning behavior by including relevant content in end-of-course examinations.…”
Section: Discussionmentioning
confidence: 99%